104. Plague Meningitis - A Systematic Review of Published Cases, Antimicrobial Treatment, and Outcomes. (4th December 2021) - Cooley, Katharine; Fleck-Derderian, Shannon; Nelson, Christina
Abstract: Background: Plague meningitis is a rare but serious manifestation of infection with the bacterium Yersinia pestis. The risk factors, clinical evolution, and optimal treatment strategies of plague meningitis are not well understood, and data is limited to sporadic case reports. To advance knowledge of this condition and support clinical practice recommendations, we conducted a systematic review of published cases of plague meningitis. Methods: We reviewed PubMed Central, Medline, Embase, and other databases for publications on plague meningitis in any language. Articles that contained reports of patients with plague meningitis plus information on patient outcome were included. Results: Among 1, 090 articles identified in our search, we found 54 articles describing 83 cases eligible for inclusion. Cases occurred between 1898 and 2015; mean age of patients was 20.5 years (range 6 wks - 64 yrs) and 65% were male. Most patients lived in the United States (23%), Argentina (18%), Vietnam (12%), or China (12%). Four patients (5%) had primary plague meningitis. More than half (59%) of patients developed meningitis secondary to primary bubonic plague; the remainder developed meningitis secondary to other or unknown forms of plague. Of patients with a bubo, 51% had an axillary bubo. The most common symptoms were fever (66%), nuchal rigidity (43%), and headache (35%); 23 patients had focal neurologic deficits such as cranial nerve abnormality. Case fatality rate was 96% (n=23/24) for patients who did not receive antimicrobial treatment and 42% (n=25/59) for patients treated with antimicrobials. Case fatality rate by antimicrobial received, including patients who received multiple antimicrobial classes, was 50% for sulfonamides (n= 38), 50% for fluoroquinolones (n=2), 19% for aminoglycosides (n=21), 11% for chloramphenicol (n=19), and 0% for tetracyclines (n=14). Conclusion: Plague meningitis has a high fatality rate, but antimicrobial treatment can improve patient outcomes. Having an axillary bubo may be a risk factor for developing plague meningitis – in contrast to our findings, a recent analysis found that only 24% of patients with bubonic plague had buboes in the axillary region. Additional research would be helpful to investigate this association further. Disclosures: All Authors : No reported disclosures